Damage evolution of thermal shock in granite for enhanced geothermal systems - Liuke Huang; Guolin Rong; Xingchuan Liao; Nailing Xiu; Haifeng Fu; Dingwei Weng; Ling Yu (Geothermics, 2026)

Screening of typical pollutants in groundwater polluted by nitrogen heterocyclic pesticides and removal mechanism of iron-doped biochar - Renchuan Fu; Kai Liu; Dan Qu; Yuqi Qi; Xiaochen Qi; Chih-Huang Weng; Yanru Hao; Na Liu; Chunyu Wen (Journal of Environmental Sciences, 2026)

Can perceptual strain index predict physiological strain? A human-participant experiment in low-intensity activity with moisture impermeable protective clothing - Sheng He; Jie Yang; Song Chen; Feifan He; Jialin Wu; Xin Zheng; Ming Fu; Yayun Li; Wenguo Weng (Building and Environment, 2026)

Recyclable hygroscopic hydrogels with dynamic networks enable efficient solar-driven atmospheric water harvesting - Fu-Yao Zhong; Chen-Xi Li; Lu-Bin Zhong; Chao-Yang Guo; George Zheng Chen; Bo Weng; Jun He; Yu-Ming Zheng (Journal of Environmental Chemical Engineering, 2026)

Transcriptome analysis revealed the characteristics of the terpenoid biosynthesis pathways and discovered two TPS-b genes in Freesia × hybrida - Shidan Weng; Xueqing Fu; Shu Li; Yu Gao; Dongshi Li; Dongqin Tang (South African Journal of Botany, 2026)

Study on thermophysiological responses for heavy-load activity in hot environment: factors interaction experiments - Sheng He; Liangchang Shen; Song Chen; Feifan He; Jie Yang; Ming Fu; Jialin Wu; Xin Zheng; Yayun Li; Wenguo Weng (Energy and Buildings, 2026)

A pine cone-inspired adaptive hydrogel for sustainable, pH-regulated lithium extraction from brine - Hui-Wen Huo; Qi-Jun Zhang; Peng Wu; Fu-Yao Zhong; Chao-Yang Guo; Bo Weng; Lu-Bin Zhong; Yu-Ming Zheng (Chemical Engineering Journal, 2026)

Construction of Kongyu 131 mutant library provides genetic resources for rice functional genomics and germplasm improvement - Tingting Xu; Qun Yang; Ran Li; Jianping Wang; Zhishan Luo; Daoyong Gong; Leihao Weng; Xiaoshan Huang; Debao Fu; Jing Li (Plant Science, 2026)

Resilience evaluation of key land use/cover types in the middle reaches of the Yellow River under flood stress: Implications for slope regulation and storage measures - Siying Yan; Baisha Weng; Shuai Zheng; Panpan Yang; Qiang Fu; Hao Wang (Journal of Hydrology, 2026)

Construction of CuO-ZnO interface electron channels accelerates the methane partial oxidation for high formaldehyde production - Yanjun Li; Chuan Yu; Chen Yang; Keke Tang; Xueyun Zhong; Sijia Weng; Chuying Qiu; Mingli Fu; Daiqi Ye (Journal of Environmental Chemical Engineering, 2026)

Rapid selection of early-maturing and low-ear position maize hybrids suitable for China using genomic prediction - Ping Luo; Wenzhe Li; Lin Zhang; Jie Yang; Houwen Wang; Fei Wang; Ruisi Yang; Xinlong Xu; Ke Yang; Hongjun Yong; Mingshun Li; Jianfeng Weng; et al. (Plant Molecular Biology, 2026)

Effects of walking activity on micro-environment heat convection and thermal comfort in chemical protective clothing - Sheng He; Jie Yang; Feifan He; Song Chen; Jialin Wu; Liangchang Shen; Xin Zheng; Ming Fu; Yayun Li; Wenguo Weng (Building and Environment, 2026)

Integrated physiological and multi-omics insights into Chlorella mutagenized by atmospheric and room temperature plasma for enhanced saline aquaculture wastewater treatment and bioresource production - Xiao-Ya Liu; Fan-Xing He; Tong-Chao Qu; Zhao-Hong Weng; Peng-Fei Li; Jie Ye; Hai-Yan Fu (Bioresource Technology, 2026)

Computer vision-assisted sorting and selective cultivation of high-activity anammox granules - Shi-Jun Li; Haoran Li; Hui-Min Fu; Yi-Cheng Wang; Xun Weng; Wei Wang; You-Peng Chen (Water Research, 2026)

Elucidating cooking-driven flavor dynamics of paddy field carp (Cyprinus carpio) using a combination of E-nose, E-tongue, GC-MS and GC-IMS - Chenying Fu; Jingying Weng; Fujing Luo; Mengxiang Liao; Lingzhan Xue; Zebin Guo (Food Chemistry, 2025)

Emulsion gels with dual antioxidant and antibacterial functions for optimized β-carotene Delivery: Utilizing phenolic acid-modified agarose - Liling Fu; Yi Ru; Qinglin Hong; Huifen Weng; Yonghui Zhang; Jun Chen; Anfeng Xiao; Qiong Xiao (Food Hydrocolloids, 2025)

Mechanisms for maintaining the stability of heterotrophic nitrification and aerobic denitrification in a synthetic microbial community under mixed nitrogen stress: Insights into community dynamics and metabolic features - Yuqi Qi; Minmin Chen; Chih-Huang Weng; Yanru Hao; Renchuan Fu; Xiao Liu; Chao Yan; Haolang Liu; Na Liu; Yaoming Su (Chemical Engineering Journal, 2025)

Interfacial water layer modulation for efficient photocatalytic CO2 reduction - Jingyi Pang; Hang Zhou; Zejiang Huang; Xiaomeng You; Beibei Xu; Xiaobin Fu; Yilong Weng; Xue-Lu Wang; Ye-Feng Yao (Chemical Engineering Journal, 2025)

Characterisation of cytochrome c oxidase-coding genes from mung bean and their response to cadmium stress based on genome-wide identification and transcriptome analysis - Yan Leng; Zhuan-Bin Niu; Shao-Hua Liu; Fu-Jun Qiao; Gui-Fang Liu; Bin Cheng; Shi-Weng Li (Molecular Biology Reports, 2025)

Injectable GelMA–PEDOT:PSS conductive hydrogel for cardiac-tissue engineering and integrated organic electrochemical transistor–based bioelectronic patch for biosensing and controlled extracellular vesicle release - Chung-Chuan Chou; Yu-Sheng Hsiao; Ming-Fu Hou; Pin-Yu Zhang; Min-Yu Hsieh; Lin-Yang Weng (Chemical Engineering Journal, 2025)

Hanging drop culture reprograms mesenchymal stem cell transcriptome to enhance cell delivery efficiency via attenuated pulmonary entrapment - Hsiang-Tzu Lee; Sheng-Yung Fu; Wei-Han Weng; Wei-Chen Chao; Yu-Pao Hsu; Nan-Ping Yang; Yu-Hsu Chen; Shau-Kwaun Chen; Chien-Wen Chang (Drug Delivery and Translational Research, 2025)
The three-dimensional (3D) culture system has emerged as an indispensable platform for modulating stem cell function in biomedicine, drug screening, and cell therapy. Despite a few studies confirming the functionality of 3D culture, the molecular factors underlying this process remain obscure. Here, we have utilized a hanging drop method to generate 3D spheroid-derived mesenchymal stem cells (3D MSCs) and compared them to conventionally 2D-cultured MSCs. The results showed that 3D MSCs exhibited distinct phenotypic features than 2D-cultured MSCs and expressed different transcriptional responses, as found from RNA-Seq analysis. Gene ontology (GO) annotations and KEGG pathway mapping pinpointed that the 3D MSCs responded more actively to incoming signals as they upregulated receptors and cytokine production while downregulating proteolysis-, cytoskeletal-, extracellular matrix-, and adhesion-related genes. Functionally, these MSCs also displayed enhanced chemotaxis and improved pulmonary transgression post-intravenous injection. This study provides mechanistic insights on addressing a significant limitation of MSC therapy: pulmonary entrapment after systemic delivery. Moreover, upregulated pluripotency-associated genes, such as Oct4, Sox2, and Nanog, suggest that the 3D MSCs possessed enhanced stemness and regenerative capacity. The results indicate that 3D spheroid culture reshapes MSC transcriptomic and functional profiles and emerges as a promising strategy for improving their therapeutic potential in regenerative medicine. Graphical abstract

Coal fly ash-based Y zeolite modified by ammonium hexafluorosilicate and its enhanced toluene adsorption under high humidity conditions - Sijia Weng; Fanghe Ye; Cha Jing; Xinyang He; Xueyun Zhong; Juntai Tian; Chen Yang; Ke Lei; Haomin Huang; Mingli Fu (Journal of Environmental Chemical Engineering, 2025)

Improving surimi gel quality by corn oligopeptide-chitosan stabilized high-internal phase Pickering emulsions - Yufeng Xue; Jiahui Song; Siyu Chen; Caili Fu; Zhanming Li; Wuyin Weng; Linfan Shi; Zhongyang Ren (Food Hydrocolloids, 2025)

Integrating microbial community dynamics and emerging contaminants (ECs) for precisely quantifying the sources in groundwater affected by livestock farming - Kai Liu; Jinrong Qiu; Chih-Huang Weng; Zhongen Tang; Renchuan Fu; Xiaojun Lin; Xiujuan Wang; Na Liu; Jingwen Zeng (Journal of Hazardous Materials, 2025)

Ellagic acid alleviates iron overload-induced liver damage by mitigating ferroptosis through modulation of the TGFβ/Smad signaling pathway - Hangjie Fu; Wenxia Li; Qimei Cheng; Zhiwei Weng; Zhiguang Huang; Lijian Zhu; Tao Ding; Bin Ding (Food Research International, 2025)

Scale drop disease virus (SDDV) triggers ferroptosis both in mandarin fish (Siniperca chuatsi) and MFF-1 cells to facilitate virus infection via linking to transferrin receptor 1 (TfR1) - Jiaming Chen; Yuting Fu; Shuyi Chen; Shaoping Weng; Jianguo He; Chuanfu Dong (Fish & Shellfish Immunology, 2025)

Degradation of 2- (2-hydroxy-5-methylphenyl) benzotriazole (UV-P) by ferrate(VI): key factors, reaction pathway, and toxicity assessment - Xiaochen Qi; Fuli Li; Chih-Huang Weng; Kai Liu; Renchuan Fu; Na Liu; Longzhen Ding (Chemical Engineering Journal, 2025)

Effects of conventional and biodegradable microplastics at comparable environmental levels on pesticide degradation in soil - Pengtao Chen; Furong Fu; Lixia Zhao; Xiaojing Li; Yang Sun; Zhenyan Fu; Liping Weng (Applied Soil Ecology, 2025)

Chemical composition, antioxidant activity, α-glucosidase inhibitory activity, and metabolomic profiling of Dendrobium officinale across diverse growing regions and cultivation modes - Shu He; Zhengli Lu; Rurui Li; Chun Chen; Xiong Fu; Kin Weng Kong; Amin Ismail; Xuechun Zhang; Zhenxing Wang (Food Bioscience, 2025)

Exploring the physical disruptions of anammox granular sludge under propylene glycol stress: Implications for nitrogen removal and long-term stability - Hui-Min Fu; Xiao-Wen Jiang; Cai-Ping Sun; Shi-Jun Li; Xun Weng; Meng-Wen Peng; Peng Yan; Xiao-Wei Xu; You-Peng Chen; Yu Shen (Journal of Water Process Engineering, 2025)

Nondestructive three-dimensional structure and growth characteristics of anammox granular sludge - Meng-Wen Peng; Ya-Song Chen; You-Peng Chen; Wan Sun; Meng-Meng Liu; Xun Weng; Shuai Wang; Yu Shen; Hui-Min Fu (International Biodeterioration & Biodegradation, 2025)

Combined Chemical-Biological Method for Efficient Clean Treatment of Oily Sludge - Qiang Fu; Xiang Liao; Weng Zhong; Yiting Yang (Water, Air, & Soil Pollution, 2025)

Evaluating overhanging slope failure mechanisms and rockfall trajectories through integrated UAV imagery and discrete element modeling - Meng-Chia Weng; Geng-Man Zhang; Yu-Yao Fu; Hoang-Khanh Le; Yu-Hui Kao (Landslides, 2025)
To evaluate the threat of rockfall from an overhanging slope above a bridge, this study proposes a comprehensive analysis procedure to assess the failure mechanisms of the slope and the associated rockfall trajectories. The analysis utilizes high-resolution point cloud data obtained through integrated UAV-based imagery technology, enabling a detailed evaluation of joint configurations and slope stability. The geometric reconstruction of unstable rock blocks, combined with stereographic projections, provides an in-depth analysis of potential failure modes. Discrete element modeling (DEM) is employed to simulate the failure processes and predict rockfall trajectories, with particular emphasis on the potential risks to the underlying bridge. The results indicate that rockfall events near the bridge are primarily driven by wedge-shaped failures, a finding confirmed by both the proposed inverted three-dimensional projection method and DEM simulations. The analysis identifies critical rock blocks near the bridge, underscoring the need for targeted mitigation strategies. This case study demonstrates the effectiveness of integrating UAV-derived data with DEM for assessing overhanging slope failures and managing rockfall risks in similar geological settings.

A Finite Element Analysis Comparing an Additive Manufacturing Lattice-Structured PEEK Implant to a Commercial Ball-and-Socket Design for Cervical Total Disc Replacement - Ming-Kai Hsieh; Fu-Cheng Kao; Yun-Da Li; De-Mei Lee; Hui Jin; Ching-Lung Tai; Tsung-Ting Tsai; Po-Liang Lai; Weng-Pin Chen (Journal of Medical and Biological Engineering, 2025)
Purpose Cervical total disc replacement (TDR) is commonly performed to treat degenerative cervical spondylosis, but it often faces challenges such as implant wear and migration. This study aimed to develop and evaluate a novel 3D-printed TDR featuring a titanium endplate and a lattice-structured poly-ether-ether-ketone (PEEK) design. The primary objective was to replicate the natural motion of the cervical disc while addressing complications associated with conventional TDRs. Methods The novel implant was created using additive manufacturing techniques, incorporating three lattice-structured PEEK designs (Cross, Octet, and Ventiles) for the nucleus pulposus and annulus fibrosus components. A finite element analysis was conducted to compare the biomechanical performance of the novel TDR with an intact cervical disc and a commercially available TDR (Baguera®C, Spineart SA, Geneva, Switzerland). Key parameters, including maximal von Mises stresses, range of motion, paths of the instantaneous center of rotation, and facet joint stresses, were evaluated under physiological loads (100 N follower load and 1.5 Nm pure moments). Results The novel 3D-printed TDR maintained structural integrity, with stresses remaining within the yield strength of PEEK. The biomechanical performance closely resembled that of an intact cervical disc, demonstrating similar ranges of motion, instantaneous center of rotation paths, and facet joint stress distributions. Conclusion The findings indicate that the innovative 3D-printed TDR may restore normal cervical spinal kinematics more effectively than existing commercial options, potentially reducing the risk of post-operative facet joint syndrome. Further experimental and clinical studies are recommended to validate these results.

Unraveling the resistance mechanism of anammox granular sludge to iron nanoparticles - Xun Weng; Meng-Jiao Gao; Zheng Mao; Hui-Min Fu; Shi-Jun Li; Peng Yan; You-Peng Chen (Journal of Environmental Management, 2025)

The impact of leak gap size and position on surgical mask performance of source control: A numerical study - Feifan He; Jialin Wu; Yayun Li; Ming Fu; Sheng He; Wenguo Weng (Building and Environment, 2025)

Overlooked emerging polycyclic aromatic hydrocarbons and benzofuran derivatives in soil from coking plant - Qiaofeng Ai; Lirong Gao; Jiyuan Weng; Xiaoying Cao; Yang Liu; Xin Cheng; Yingxin Zhang; Qianling Yang; Meijun Li; Jing Yang; Qiang Fu; Xuan Zheng; et al. (Science of The Total Environment, 2024)

National investigation of bisphenols in the surface soil in China - Chang-Yu Weng; Ying-Ying Zhang; Fu-Jie Zhu; Shi-Ming Jia; Wan-Li Ma (Science of The Total Environment, 2024)

Bio-inspired sustainable electrospun quantum nanostructures for high quality factor enabled face masks and self-powered intelligent theranostics - Loganathan Veeramuthu; Ren-Jie Weng; Wei-Hung Chiang; Archana Pandiyan; Fu-Jie Liu; Fang-Cheng Liang; G. Ranjith Kumar; Hua-Yi Hsu; Yu-Ci Chen; Wen-Yinn Lin; Yao-Chun Tang; Wan-Rong Lin; et al. (Chemical Engineering Journal, 2024)

Experimental and Numerical Investigation on Interaction Mechanism Between Hydraulic Fracture and Natural Fracture - Haifeng Fu; Liuke Huang; Bing Hou; Dingwei Weng; Baoshan guan; Taixian Zhong; Yulong Zhao (Rock Mechanics and Rock Engineering, 2024)

Autophagy in Acute Lung Injury - Danjuan Liu; Shuoyun Weng; Chunjin Fu; Rongjie Guo; Min Chen; Bingbing Shi; Junting Weng (Cell Biochemistry and Biophysics, 2024)

Performance evaluation and microbial community succession analysis of co-composting treatment of refinery waste activated sludge - Xinge Fu; Hui Zuo; Yibin Weng; Zhouhao Wang; Yue Kou; Dingyuan Wang; Zhuoyu Li; Qinghong Wang; Muhammad Arslan; Mohamed Gamal El-Din; Chunmao Chen (Journal of Environmental Management, 2024)

Valence electronic engineering of hollow-nanocube-structured CoFeNi-layered double hydroxides for highly efficient oxygen evolution - Lu Liu; Lingxing Zan; Yunchuan Tu; Hongling Zhang; Dan Zhu; Zhe Li; Jiawen Zheng; Zhuangzhuang Zhang; Yu Sun; Qiang Weng; Jian Li; Qingbo Wei; et al. (Chemical Engineering Journal, 2024)

In-situ fabrication of defect rich Cu2+1O on electrodeposited Cu cone arrays for promoting electrocatalytic anode hydrogen production - Yanhong Weng; Huanhua You; Danni Liu; Hao Chen; Hao Lin; Guodong Fu; Fengzhan Si; Jiujun Zhang; Xian-Zhu Fu; Jing-Li Luo (Chemical Engineering Journal, 2024)

A feature extractor for temporal data of electronic nose based on parallel long short-term memory network in flavor discrimination of Chinese vinegars - Yufei Chen; Jun Fu; Xin Weng; Jiaoni Chen; Ruifen Hu; Yunfang Zhu (Journal of Food Engineering, 2024)

Review on the Role of Mitochondrial Dysfunction in Septic Encephalopathy - Chunjin Fu; Shuoyun Weng; Danjuan Liu; Rongjie Guo; Min Chen; Bingbing Shi; Junting Weng (Cell Biochemistry and Biophysics, 2024)

Active packaging coating based on agarose grafted with benzoic acid derivatives: Preparation, characterization and application in fish preservation - Liling Fu; Yi Ru; Jinming Ye; Qinglin Hong; Huifen Weng; Yonghui Zhang; Jun Chen; Anfeng Xiao; Qiong Xiao (Food Hydrocolloids, 2024)

Shear-induced permeability evolution of natural fractures in granite: Implications for stimulation of EGS reservoirs - Xuefeng Li; Fengshou Zhang; Nailing Xiu; Dingwei Weng; Bo Cai; Haifeng Fu (Engineering Geology, 2024)

The role of galectins in the regulation of autophagy and inflammasome in host immunity - Tzu-Han Lo; I-Chun Weng; Hung-Lin Chen; Fu-Tong Liu (Seminars in Immunopathology, 2024)

Integrated Bulk and Single-Cell RNA-Sequencing Reveals the Effects of Circadian Rhythm Disruption on the Metabolic Reprogramming of CD4+ T Cells in Alzheimer’s Disease - Weipin Weng; Jianhan Fu; Fan Cheng; Yixuan Wang; Jie Zhang (Molecular Neurobiology, 2024)

Construction of 2D/2D NH2-TiO2/ReS2 molecular-connected heterojunction to achieve selective carrier transport for photocatalytic hydrogen production - Huihui Weng; Houjiang Liu; Guijun Yang; Jiawei Ding; Chuangchuang Gong; Yuanyuan Fu; Jin Cui; Liying Ma; Chunnian He; Naiqin Zhao; Fang He (Chemical Engineering Journal, 2024)

Efficiency and mechanism of enhanced norfloxacin removal using amorphous TiO2-modified biochar - Yu-liang Hu; Ying Liu; Weng Fu; Hong Yang (Environmental Pollution, 2024)

New insights into functional divergence and adaptive evolution of uncultured bacteria in anammox community by complete genome-centric analysis - Yi-Cheng Wang; Yanping Mao; Hui-Min Fu; Jin Wang; Xun Weng; Zi-Hao Liu; Xiao-Wei Xu; Peng Yan; Fang Fang; Jin-Song Guo; Yu Shen; You-Peng Chen (Science of The Total Environment, 2024)

Self-assembled oxygen vacancies modified hierarchical hollow tubular Bi2WO6/In2O3 Z-scheme heterojunction for optimized photocatalytic degradation of norfloxacin - Xin Wang; Chuangyun Guo; Xinru Hu; Yifei Xu; Cheng Zhang; Jiamin Wei; Jushi Weng; Yilan Liu; Lianshe Fu; Qing Wang; Tinghai Yang (Journal of Environmental Chemical Engineering, 2024)

Punching shear behavior and corrosion resistance of composite slab-column connections reinforced by BFRP and steel rebar - Kai Qian; Yun-Hao Weng; Shi-Lin Liang; Feng Fu (Engineering Structures, 2024)

Motility behavior and physiological response mechanisms of aerobic denitrifier, Enterobacter cloacae strain HNR under high salt stress: Insights from individual cells to populations - Meng Cheng; Hui-Min Fu; Zheng Mao; Peng Yan; Xun Weng; Teng-Fei Ma; Xiao-Wei Xu; Jin-Song Guo; Fang Fang; You-Peng Chen (Science of The Total Environment, 2024)

Combined pollution and soil microbial effect of pesticides and microplastics in greenhouse soil of suburban Tianjin, Northern China - Furong Fu; Yang Sun; Dan Yang; Lixia Zhao; Xiaojing Li; Liping Weng; Yongtao Li (Environmental Pollution, 2024)

MMBERT: a unified framework for biomedical named entity recognition - Lei Fu; Zuquan Weng; Jiheng Zhang; Haihe Xie; Yiqing Cao (Medical & Biological Engineering & Computing, 2024)

Fate of iron nanoparticles in anammox system: Dissolution, migration and transformation - Xun Weng; Hui-Min Fu; Zheng Mao; Peng Yan; Xiao-Wei Xu; Yu Shen; You-Peng Chen (Journal of Environmental Management, 2023)

Shikonin promotes ferroptosis in HaCaT cells through Nrf2 and alleviates imiquimod-induced psoriasis in mice - Zhiwei Weng; Hangjie Fu; Zhiguang Huang; Wenxia Li; Yixin Xie; Jianchang Yuan; Bin Ding (Chemico-Biological Interactions, 2023)

Transcriptome Analysis Revealed the Differential Molecular Response Mechanisms of Roots, Stems, and Leaves in Mung Bean to Cadmium Stress - Ping-min Wu; Yan Leng; Shi-Weng Li; Yu-Lin Wang; Fu-Jun Qiao (Journal of Plant Growth Regulation, 2023)

Development and characterization of a spleen cell line from yellowfin seabream Acanthopagrus latus and its susceptibility to Mandarinfish ranavirus - Zhipeng Zhan; Jiajie Fu; Huiquan Chen; Hongbo Pan; Shaoping Weng; Jianguo He; Changjun Guo (Journal of Fish Diseases, 2023)
Yellowfin seabream ( Acanthopagrus latus ) is one of the most commercially important marine fish in China. In this study, a new continuous cell line, named ALS cells, was developed from the spleen tissue of A. latus . The cell line was maintained in Dulbecco's modified Eagle medium/Nutrient Mixture F‐12 Ham (DMEM/F‐12) supplemented with 10% fetal bovine serum (FBS) and successfully cultured up to 50 passages. The cell line was authenticated by amplifying and sequencing mitochondrial cytochrome C oxidase subunit‐I ( coi‐I ) gene. The ALS cell line had the maximum growth rate in DMEM/F‐12 medium containing 20% FBS at 27°C. Chromosome number analysis showed that the ALS cells have a modal diploid chromosome number of 34. The ALS cell line was transfected with the pEGFP‐N1 plasmid, and green fluorescence was observed. The ALS cell line was used for testing Mandarinfish ranavirus (MRV) susceptibility, and the cytopathic effects in the cell line were observed at 4 days post‐infection (dpi). Furthermore, the susceptibility of the ALS cell line to MRV and the levels of MRV mRNA and viral loads were found to be significantly increased at 1–7 dpi. This study revealed that the ALS cell line could be useful for molecular, virological, and biotechnological studies on yellowfin seabream.

Towards system-theoretic risk management for maritime transportation systems: A case study of the yangtze river estuary - Shanshan Fu; Siyuan Gu; Yue Zhang; Mingyang Zhang; Jinxian Weng (Ocean Engineering, 2023)

Non-target and target analysis to identify and characterize thiophenes in soil from an abandoned coking plant - Qiaofeng Ai; Lirong Gao; Di Huang; Jing Yang; Qiang Fu; Xuan Zheng; Yang Liu; Lin Qiao; Jiyuan Weng; Minghui Zheng (Journal of Hazardous Materials, 2023)

AIWW: a new nutrition-screening tool for the oncologic population - Yi-Zhong Ge; Zhen-Ming Fu; Qi Zhang; Meng-Meng Song; Guo-Tian Ruan; Xi Zhang; Xiao-Wei Zhang; Xiang-Rui Li; Kang-Ping Zhang; Meng Tang; Xiao-Yue Liu; Ming Yang; et al. (Science China Life Sciences, 2023)

Active packaging coatings based on agarose caffeate: Preparation, characterisation, and application in grass carp (Ctenopharyngodon idellus) preservation - Liling Fu; Yi Ru; Qinglin Hong; Yonghui Zhang; Huifen Weng; Qiuming Yang; Qiong Xiao; Anfeng Xiao (Food Packaging and Shelf Life, 2023)

Sialylation of cell surface glycoconjugates modulates cytosolic galectin-mediated responses upon organelle damage - I-Chun Weng; Hung-Lin Chen; Wei-Han Lin; Fu-Tong Liu (Glycoconjugate Journal, 2023)

A mandarinfish Siniperca chuatsi infection and vaccination model for SDDV and efficacy evaluation of the formalin-killed cell vaccine in yellowfin seabream Acanthopagrus latus - Yuting Fu; Yong Li; Jiaming Chen; Fangzhao Yu; Xiangrong Liu; Weixuan Fu; Hongrun Pan; Wangdong Li; Shaoping Weng; Jianguo He; Chuanfu Dong (Aquaculture, 2023)

Amyloid protein fibrils show enhanced ice recrystallization inhibition activity when serve as pickering emulsion stabilizer - Yuying Fu; Yuan Li; Shuni Weng; Wenhui Qi; Huanhuan Su; Teng Li (Food Hydrocolloids, 2023)

Numerical study of transient indoor airflow and virus-laden droplet dispersion: Impact of interactive human movement - Jialin Wu; Wenguo Weng; Ming Fu; Yayun Li (Science of The Total Environment, 2023)

Association between blood metal exposures and hyperuricemia in the U.S. general adult: A subgroup analysis from NHANES - Yuxuan Tan; Yingyin Fu; Feng Huang; Lin Wen; Xueqiong Weng; Huojie Yao; Huanzhu Liang; Mincong Kuang; Chunxia Jing (Chemosphere, 2023)

Effectively protecting Asian seabass Lates calcarifer from ISKNV-I, ISKNV-II, RSIV-II and SDDV by an inactivated ISKNV-I and SDDV bivalent vaccine - Yuting Fu; Yong Li; Wenfeng Zhang; Weixuan Fu; Wangdong Li; Zhiming Zhu; Shaoping Weng; Jianguo He; Chuanfu Dong (Aquaculture, 2023)

Assessing the impact of rockfall on a bridge by using hybrid DEM/FEM analysis: A case study in Central Taiwan - Terry Y.P. Yuen; Meng-Chia Weng; Yu-Yao Fu; Guan-Ting Lu; Wen-Jie Shiu; Cheng-An Lu; Chun-Yuan Liu; Chia-Chi Chiu; Tzu-Han Wen (Engineering Geology, 2023)

Production and characterization of monoclonal antibodies against mandarinfish ranavirus and first identification of pyloric caecum as the major target tissue - Wenfeng Zhang; Hengwei Deng; Yuting Fu; Weixuan Fu; Shaoping Weng; Jianguo He; Chuanfu Dong (Journal of Fish Diseases, 2023)
Mandarinfish ranavirus (MRV), also known as a variant of largemouth bass virus (LMBV), is an emerging pathogen in mandarinfish aquaculture. In this study, monoclonal antibodies (mAbs) against MRV were produced and characterized, and 7 mAbs were obtained through Western blotting screening and all 7 mAbs specifically recognized MRV/LMBV but not several piscine iridoviruses as ISKNV, GIV and TFV. By LC MS/MS analysis, the recognized viral proteins by seven mAbs were identified as MRV‐pORF47L, MRV‐pORF55R, MRV‐pORF57L, MRV‐pORF77L and MRV‐pORF78L, respectively, and all five viral proteins are late expression structural proteins by Western blotting. Based on mAb 1C4, immuno‐histochemistry and immuno‐histo‐fluorescence were performed to re‐assess the tissue tropism of MRV. The result showed that abundant reactive signals were observed in infected spleen, kidney as well as intestine and pyloric caecum. Real‐time quantitative PCR also demonstrated that spleen as well as pyloric caecum and intestines are the major target tissue upon MRV infection. In infected intestines and pyloric caecum, numerous enlarged, multinucleated cells with intracytoplasmic inclusions were identified as the target cells of MRV, suggesting that MRV serves as a digestive tract pathogen to mandarinfish, which may explain why acute infection of MRV can cause the typical clinicopathology featured by severe ascites.

Towards effective wildlife protection law for marine species in China: A stakeholders’ perspective - Kit Yue Kwan; Ruifang Chen; Chun-Chieh Wang; Shuhao Lin; Lv Wu; Xiaoyong Xie; Zhaohong Weng; Menghong Hu; Haichao Zhou; Zhou Wu; Yijian Fu; Wenquan Zhen; et al. (Frontiers in Marine Science, 2023)
Introduction As one of the megadiverse countries, the effectiveness of wildlife protection in China is of great significance to global biodiversity conservation. With continued evolution and revisions, China’s Wildlife Protection Law has listed over 140 marine species; however, it is still inclined toward terrestrial animals. Methods To narrow the gap between compliance and enforcement, we collected 1,309 effective responses from various coastal cities of China through an anonymous online questionnaire survey, to investigate their exposure, understanding and attitudes toward Wildlife Protection Law for marine species (mWPL). Results Most respondents demonstrated an overall good understanding about the context, necessity and effectiveness of mWPL. The fisher communities were found to be more aware of the dissemination and implementation of mWPL. However, they understood less of the penal system, and exhibited negative attitudes toward the necessity and punishment of the legislation, probably due to the conflicts between resource utilizations and legislative interventions. The participants also indicated that seahorses, horseshoe crabs and corals were commonly subjected to illegal exploitations. Discussion While most respondents suggested greater fines, tighter laws and better public enforcement, we advocate the exploration of bottom-up options such as community engagement and environmental education to improve compliance and implementation of mWPL for the benefit of marine wildlife conservation in China.

Enhancement of hydrogen clean energy production from greenhouse gas by in-situ hydrogen separation with a cobalt-silica membrane - Guozhao Ji; Xian Yin; Weng Fu; Xiaonan Kou; Dachamir Hotza; Yinxiang Wang; Aimin Li; Gianni Olguin; Weijian Wang (Journal of Cleaner Production, 2023)

A numerical tool for assessing human thermal safety and thermal comfort in cold-weather activities - Feiyu Chen; Ming Fu; Yayun Li; Shifei Shen; Jie Yang; Wenguo Weng (International Journal of Biometeorology, 2023)

Uranium capture by a layered 2D/2D niobium phosphate/holey graphene architecture via an electro-adsorption and electrocatalytic reduction coupling process - Yun Liao; Ruilin Lei; Xiaofang Weng; Chuan Yan; Jiaxi Fu; Guoxing Wei; Chen Zhang; Meng Wang; Hongqing Wang (Journal of Hazardous Materials, 2023)

Machine Learning-Enabled Determination of Diffuseness of Brain Arteriovenous Malformations from Magnetic Resonance Angiography - Yuming Jiao; Jun-Ze Zhang; Qi Zhao; Jia-Qi Liu; Zhen-Zhou Wu; Yan Li; Hao Li; Wei-Lun Fu; Jian-Cong Weng; Ran Huo; Shao-Zhi Zhao; Shuo Wang; et al. (Translational Stroke Research, 2022)

Evaluating the Effect of Anisotropy on Hydraulic Stimulation in a Slate Geothermal Reservoir - Meng-Chia Weng; Po-Lin Wu; Chih-Hung Fang; Yu-Yao Fu; Yen-Che Liao; Chih-Hsi Liu (Rock Mechanics and Rock Engineering, 2022)

Assessing the impact of rockfall on the retaining structures of a mountain road: a case study in Taiwan - Che-Ming Yang; Chung-Hsun Lee; Chun-Yuan Liu; Wei-Kai Huang; Meng-Chia Weng; Yu-Yao Fu (Landslides, 2022)

Outburst debris flow of Yusui Stream caused by a large-scale Silabaku landslide, Southern Taiwan - Che-Ming Yang; Wei-An Chao; Meng-Chia Weng; Yu-Yao Fu; Jui-Ming Chang; Wei-Kai Huang (Landslides, 2022)

Influence of surface cracks on temperature response of concrete under constant climate environment - Jian-Hua Jiang; Yong-Quan Fu; Fei-Fei Hu; Wei-Xin Weng (European Journal of Environmental and Civil Engineering, 2021)

Automatic Striatal ROI Delineation for Semi-quantitative Analysis of 99mTc-TRODAT-1 Brain SPECT Imaging - Bang-Hung Yang; Kang-Ping Lin; Mei-Fen Chen; Jui-Hung Weng; Pan-Fu Kao; Wen-Chen Lin; Ren-Shyan Liu (Journal of Medical and Biological Engineering, 2020)

Engineering SrCuxO composition to tailor the degradation activity toward organic pollutant under dark ambient conditions - Huihuang Chen; Weng Fu; Yulin Xing; Jinxuan Zhang; Jiangang Ku (Environmental Science and Pollution Research, 2019)

Investigation on synthesis of ion-imprinted mesoporous adsorbents by using ultrasound- and microwave-assisted preparation and their dynamic adsorption properties on heavy metals - Hong Yang; Yanling Hu; Xiaoyu Wang; Weng Fu; Huijuan Tian; Easar Alam (Environmental Science and Pollution Research, 2019)

Responses of urban heat island in Atlanta to different land-use scenarios - Peng Fu; Qihao Weng (Theoretical and Applied Climatology, 2018)

Optimized decellularization protocol including α-Gal epitope reduction for fabrication of an acellular porcine annulus fibrosus scaffold - Lien-Chen Wu; Yi-Jie Kuo; Fu-Wen Sun; Chia-Hsien Chen; Chang-Jung Chiang; Pei-Wei Weng; Yang-Hwei Tsuang; Yi-You Huang (Cell and Tissue Banking, 2017)

Fine mapping identifies CsGCN5 encoding a histone acetyltransferase as putative candidate gene for tendril-less1 mutation (td-1) in cucumber - Feifan Chen; Bingbing Fu; Yupeng Pan; Chaowen Zhang; Haifan Wen; Yiqun Weng; Peng Chen; Yuhong Li (Theoretical and Applied Genetics, 2017)

Erratum to: The Rho kinase inhibitor, fasudil, ameliorates diabetes-induced cardiac dysfunction by improving calcium clearance and actin remodeling - Dongwu Lai; Jing Gao; Xukun Bi; Hong He; Xiaolu Shi; Shaoxiang Weng; Yu Chen; Ying Yang; Yang Ye; Guosheng Fu (Journal of Molecular Medicine, 2017)

The Rho kinase inhibitor, fasudil, ameliorates diabetes-induced cardiac dysfunction by improving calcium clearance and actin remodeling - Dongwu Lai; Jing Gao; Xukun Bi; Hong He; Xiaolu Shi; Shaoxiang Weng; Yu Chen; Ying Yang; Yang Ye; Guosheng Fu (Journal of Molecular Medicine, 2017)

Isolation of marine bacteria with antimicrobial activities from cultured and field-collected soft corals - Yu-Hsin Chen; Jimmy Kuo; Ping-Jung Sung; Yu-Chia Chang; Mei-Chin Lu; Tit-Yee Wong; Jong-Kang Liu; Ching-Feng Weng; Wen-Hung Twan; Fu-Wen Kuo (World Journal of Microbiology and Biotechnology, 2012)

The effects of elicitation on the expression of key enzyme genes and on production of tropane alkaloids in Anisodus acutangulus plant - Xiuqin Luo; Shiqiu Weng; Xiaoling Ni; Xiaoyun Wang; Xueqing Fu; Jianbo Xiao; Guoyin Kai (Biologia, 2012)

Characterization of a thermostable alkaline phytase from Bacillus licheniformis ZJ-6 in Pichia pastoris - Qian Wang; Shi-Jun Fu; Jian-Yi Sun; Xiao-Yan Weng (World Journal of Microbiology and Biotechnology, 2011)

Hypoxia-induced compensatory effect as related to Shh and HIF-1α in ischemia embryo rat heart - Jin-Ming Hwang; Yi-Jiun Weng; James A. Lin; Da-Tian Bau; Fu-Yang Ko; Fuu-Jen Tsai; Chang-Hai Tsai; Chieh-Hsi Wu; Pei-Cheng Lin; Chih-Yang Huang; Wei-Wen Kuo (Molecular and Cellular Biochemistry, 2008)